Analysis of Receiving System in the Operational Activities of Lombok Astoria Hotel - Reyza Afriyan Yudhananto; Iman Waskito (Jurnal Riset Mahasiswa Akuntansi, 2026)
This study aims to analyze the receiving system within the operational activities of Hotel Lombok Astoria and to evaluate its effectiveness as part of the hotel’s internal control mechanisms. The research employed a descriptive qualitative approach through direct observation, in-depth interviews, and documentation of the receiving process. The informants consisted of staff involved in the procurement workflow, including the Purchasing, Receiving, Storekeeping, and Accounting departments. The collected data were analyzed through the stages of data reduction, presentation, and conclusion drawing to provide an accurate depiction of how the receiving procedures are implemented in practice. The findings indicate that the hotel’s receiving system functions adequately with a structured workflow, beginning from document verification and physical inspection of goods to data entry into the Visual Hotel Program system and the preparation and storage of receiving documents. However, several challenges were identified, particularly related to staff understanding of procedures, limited data integration between departments, and the need for improved arrangement of temporary storage areas. These findings highlight the importance of strengthening standard operating procedures, enhancing staff competencies, and optimizing storage management to ensure a more accurate, efficient, and well-controlled receiving process that supports overall internal control within the hotel.